The captive - Burrowes, Grace (Burrowes, Grace. Captive hearts, 2014)
Struggling with Society life, Christian Severn, who lost his wife, son and will to live, finds an ally in the Countess of Windmere, who helps him stay strong for his surviving daughter, but refuses his proposal of marriage even though romance has blossomed between them.